Parler et penser en équipe l'admission et l'accompagnement éducatif d'enfants placés au regard de leur situation extrême - Vincent Chaudet
Based on our thesis works, this article asks the question of how to make readable and intelligible the specialized educational activity in favour of children and adolescents experiencing by extreme situations (Fischer, 1994) and whose vulnerability is one of the components. The inductive approach used, based on some cases encountered, led to admission commission being considered as a working instance revealing underlying stakes. The investigation carried out at the heart of a commission in exercise, followed by interviews in self-confrontation inspired by the clinic of the activity (Clot, 2001) made it possible to update the discursive dynamic of professionals in take with some emotional stakes, psychosocial and hermeneutic that provide information on their real activity. The discussion opened about vulnerability ultimately leads to specify the extreme dimension of vulnerability of the public concerned and the revision of the educational posture to be carried out.